ACTIVITY AND EFFECTIVENESS OF REGIONAL CURRENCY-CREDIT AND FINANCIAL ORGANIZATIONS - Mamayusupova , Shakhina Ulugbek kizi (Educational Research in Universal Sciences, 2023)
The process of globalization is the growth of trade, the specialization and expansion of world production, the international current development of capital, the international movement of services and products. Created the ground for the development of international finance. danger, the state of global financial markets, the state of corporate governance, the management of interstate relations and economic activity led to complications. International finance has an objective basic represents relationships. The material basis of international finance international fincancial flows between countries, including cash flows - payments for imported products and services, as well as products and services foreign exchange earnings from exports, these flows are economic.